Strategi Pembangunan Melalui Pengarusutamaan Gender (Analisis SWOT pada Program Gender Watch di Kabupaten Gresik) - Rabina Yunus (Universitas Bandar Lampung (UBL), 2015)
This research aimed (1) to analyze the alternative of the development strategy resulted from the SWOT analysis at the Gender Watch Program in Gresik Regency; and (2) to analyze the constraints faced during the implementation of the program.The research used qualitative case study with the techniques of interviews, observation and documentation in collecting the data.The research results revealed that the Local government of Gresik Regency had greater strength and opportunity factors compared to the weakness and threats; consequently, the strategy used comprised the strong desires of the Local government of Gresik Regency , the financial resources they had in order to realize the opportunity, which was the local development through the gender maincurrent in Gresik Regency. The constraints faced in the implementation of the program comprised the strong patriachal culture/tradition of the community and the economic factors.Therefore, the strong cooperation beetwen the Local government and the Village Government was needed in order to solve the problems which could become constraints in implementing the program.